2011
DOI: 10.1021/mp200096r
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Apical Transporters Expressed in Rat Proximal Tubular Cells (PTCs) in Primary Culture

Abstract: Since in vitro cell culture models often show altered apical transporter expression, they are not necessarily suitable for the analysis of renal transport processes. Therefore, we aimed here to investigate the usefulness of primary-cultured rat proximal tubular cells (PTCs) for this purpose. After isolation of renal cortical cells from rat kidneys, PTCs were enriched and the gene expression and function of apical transporters were analyzed by means of microarray, RT-PCR and uptake experiments. RT-PCR confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Similar characteristics of carnitine transport have been observed in brush‐border membrane vesicles isolated from kidney cortex . In kidney epithelial cells in primary culture, sodium dependence of carnitine uptake from the luminal side across the apical membrane has been reported in rats and humans . Sodium ion‐dependent electrogenic transport is consistent with reabsorptive transport at the renal tubules.…”
Section: Role Of Octn2 In Carnitine Transport In Somatic Tissuessupporting
confidence: 73%
“…Similar characteristics of carnitine transport have been observed in brush‐border membrane vesicles isolated from kidney cortex . In kidney epithelial cells in primary culture, sodium dependence of carnitine uptake from the luminal side across the apical membrane has been reported in rats and humans . Sodium ion‐dependent electrogenic transport is consistent with reabsorptive transport at the renal tubules.…”
Section: Role Of Octn2 In Carnitine Transport In Somatic Tissuessupporting
confidence: 73%
“…The notable difference in polymyxin B susceptibility between A549 and HK-2 cells may be due to the differential expression of membrane transporters such as megalin, which exists in the latter but not in lung epithelial cells (26). Very likely, uptake of polymyxins is mainly by PEPT2 in A549 cells (27) and by both PEPT2 and megalin in HK-2 cells (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of mitochondrial proapoptotic proteins such as cytoplasmic cytochrome C and Bax was increased. It has been reported that p53 is an important transcription factor involved in regulation of mitochondrial apoptosis and that it can regulate the permeability of the outer membranes of mitochondria [ 19 ]. Therefore, the protein expression, intracellular distribution, and acetylation level of p53 in the renal cortex after HS/R were measured.…”
Section: Discussionmentioning
confidence: 99%
“…The other portion of kidney tissue was used for isolation of RTECs by a method described previously, with slight modifications [ 19 , 20 ]. Briefly, the cortex was cut into fragments.…”
Section: Methodsmentioning
confidence: 99%